Sufism and Interreligious Dialogue: The Naqshbandi Haqqani Sufi Order in Indonesia - Wahyu Nugroho (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2021)
Sufism plays a vital role in the process of spreading Islam in Indonesia, the key factor being inclusion and tolerance. Nowadays, the tolerant spirit of Sufi Islam is more and more challenged by certain intolerant Salafi groups. It seems that some Sufi groups in Indonesia have unfortunately adopted some of their attitudes and have become increasingly wary of other religions and unwilling to engage with them in a constructive dialogue. This negative trend creates tension within the Muslim community and in Indonesian society at large. After all, Indonesia is a country that is built on the principles of religious plurality. This article explores the teachings and practices of the Naqshbandi Haqqani Sufi order and their understanding of religious plurality. The study found that—despite the existing Salafi trend— the Naqshbandi shaykhs continue to praise religious plurality as one of God’s blessings. In their view, the sincere engagement in interreligious dialogue allows their followers to experience and actualize God’s Love. The Naqshbandi order also actively engages in interreligious dialogue with other communities in Jakarta and Kartasura.